ANALISA : Journal of Social Science and Religion - Tauseef Ahmad Parray (Office of Religious Research and Development Ministry of Religious Affairs Semarang, 2016)
No. Penulis --- Judul Artikel --- Halaman --- 1. Tauseef Ahmad Parray --- Recent Scholarship on ?Islamism? Discourse : An Evaluation and Assesment --- 1-18 --- 2. Zakiyah --- The Chronicle of Terrorism and Islamic Militancy in Indonesia --- 19-40 --- 3. Arifuddin Ismail --- New Religious Movement on Campus : A Role of Campus? Mosques in Raising Exclusivity (A Case at Gadjah Mada University, Yogyakarta) --- 41-58 --- 4. Betty Mauli Rosa Bustam --- The Society of Minangkabau in Tulis Sutan Sati?s Sengsara Membawa Nikmat : Between Local Traditions And Islamic Teachings --- 59-74 --- 5. Asep Nahrul Musadad --- Tracing The ?Cultural Changes? in Sundanese Local Incantations --- 75-90 --- 6. Siti Sholihati, Heddy Shri Ahimsa-Putra, Heru Nugroho --- The Uses of Religious Symbols to Represent Islam (A Study on Religious Soap Opera ?Bukan Islam KTP?) --- 91-104 --- 7. Napsiah, Budhi Gunawan, Oekan Soekotjo Abdoellah, dan Munandar Sulaeman --- Value Rationality of People Living on The Slope of Merapi in Yogyakarta --- 105-120 --- 8. Mahfud Junaedi --- Imam Hatip School (Imam Hatip Lisesi) : Islamic School in Contemporary Secular Turkey --- 121-138